The Role of School Operators in Data and Information System Management and Service to Improve School Quality - Emelia Rosana (CV. ADIBA AISHA AMIRA, 2022)
Education today requires a foundation that must be built, namely realizing its position as a producer of educational services. Schools must understand well the increasingly complex needs of society, especially following the very rapid development of IT information. The research with the title